PENINGKATAN LITERASI SAINS MENGGUNAKAN MEDIA AJAR AUDIO VISUAL BERBASIS GUBAHAN LAGU - Purwasari, Endang; Yunanto, Rian Prasetya; Nugroho, Widhi; Utami , Citra Dewi (Abdi Seni, 2025)
One of the interventions to improve the quality of basic education that can be carried out by higher education is through the implementation of Community Service (PKM) programs. PKM is ISI Surakarta's which focuses on art for the community as an alternative solution to the problems faced by the community. The problem faced is a change in the curriculum which requires teachers to innovate in developing learning media. Six State Elementary Schools in Andong District are the targets of this service activity. All of them have a mission to make learning fun, one of which is through singing activities. Teaching media in audio-visual format has been proven to be able to increase students' learning motivation, but the limited abilities of teachers are an obstacle to innovation. Therefore, training in the production of audio-visual teaching media is very necessary considering that students' scientific literacy competency levels need to be increased.